Exploring China stepping into the dawn of chemical pesticide-free agriculture in 2050 - Wang, Xuejiang; Chi, Yan; Li, Feng (Frontiers in Plant Science, 2022)
China has implemented a series of policies to reduce the usage of chemical pesticide to maintain food production safety and to reduce water and soil pollution. However, there is still a huge gap in developing biological pesticides to replace chemical agents or managing pests to prevent crop production loss. It is necessary to predict the future use of chemical pesticides and to exploit the potential ways to control pests and crop diseases. Pesticide usage is affected by seasonal changes and analyzed by using a seasonal ARIMA (An autoregressive integrated moving average) model (a statistical model that predicts future trends by using time-series data). The future development of biopesticides in China was predicted by using the compound annual growth rate (CAGR), which is calculated via the equation ((Final value/Starting value)1/years-1) according to the annual growth rate of target products over time. According to the reducing trend of pesticide and biological pesticide usage annually, China is predicted possibly step into the era of pesticide-free agriculture in 2050 based on the analysis of ARIMA model. With CAGR calculation, China will produce from 500 thousand to one million tons of biopesticides in 2050, which can meet the need to replace chemical pesticides in agriculture to prevent the present crop production loss. To achieve the goal, China still has the greatest challenges to develop biopesticides and use various strategies to control pest and crop diseases. China may step into the dawn of chemical pesticide-free agriculture in 2050 if biopesticides can be developed smoothly and pests can be controlled well using various strategies.